Violation and confirmation of the law: he intricate effects of the invocation of the law in armed conflict - Marxsen, Christian (MPIL research paper series, 2017)
Within the jus contra bellum there is an apparent contradiction between states’ verbal commitments to the law and the prevalence of armed conflicts. Taking this contradiction as a starting point, this article aims to provide empirical insights into how states invoke international law to justify their participation in armed conflicts. It develops a typology of how law can be confirmed by its invocation, taking an inductive approach based on case analysis. Do recent military interventions indicate a decline of international law? This article argues that there are three dimensions of confirmation. Firstly, law can be confirmed as an instrument of communication between states. Secondly, in a set of uncontroversial cases, the specific substantive rules of international law are confirmed through what is described as coherent practice. Thirdly, the article explains why even in controversial cases substantive rules may be confirmed through their invocation, even where the action is in fact illegal